A Preliminary Review on Conservation Status of Shivalik Landscape in Northwest India - Sivakumar, K.; Sathyakumar, S.; Rawat, G. S. (Indian Forester, 2010)
The Shivalik landscape is extended from the Indus basin to the Brahmaputra with one gap of over 300 km from the Sapta Kosi to the Manas River. The Shivalik landscape, has been categorized under Indo-Gangetic plains and it has special significance in India's biogeography due to intermingling of taxa from the Indo-Malayan and Palaearctic regions. In the Northwest part of Shivaliks, a total of 21 wildlife protected areas had been established in six States and one Union Territory covering up to ca 2500 km2. Though, more than 80% of existing protected areas of Shivaliks are in the Northwest Shivaliks, it is yet to cover some of the unique biodiversity of this region. Shivaliks in Jammu and Kashmir, Punjab, Haryana and Chandigarh are comparatively not well represented in the existing PA network of this region. Wildlife Divisions of Ropar, Hoshiarpur and Gurdaspur in Punjab, and the catchment area of Sukhna Lake in Chandigarh have been identified as potential Community/Conservation Reserves. Moreover, four clusters of Protected Areas such as 1) Kashmir, 2) Punjab and Chandigarh, 3) Himachal and Haryana, and 4) Uttarakhand have been identified in this region which may be reviewed and linked through available wildlife corridors. Of the identified four clusters of Protected Areas, two clusters require bilateral cooperation between two States for better coordination and management.